2012
DOI: 10.1186/1742-2094-9-203
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and function of the human macrophage dopaminergic system: implications for CNS disease and drug abuse

Abstract: BackgroundPerivascular macrophages and microglia are critical to CNS function. Drugs of abuse increase extracellular dopamine in the CNS, exposing these cells to elevated levels of dopamine. In rodent macrophages and human T-cells, dopamine was shown to modulate cellular functions through activation of dopamine receptors and other dopaminergic proteins. The expression of these proteins and the effects of dopamine on human macrophage functions had not been studied.MethodsTo study dopaminergic gene expression, q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
92
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 83 publications
7
92
1
Order By: Relevance
“…Besides, dopamine significantly increased the levels of the chemokine IL-8 in THP-1 macrophages, which is similar to the observations made by Gaskill [11] in LPS-stimulated human mononuclear-derived macrophages. The stimulatory effect of dopamine on the secretion of IL-8 was partially reversed by the β-adrenergic blocker propranolol, similar to the effect previously described in keratinocytes, where dopamine stimulated the production of IL-6 and IL-8 mainly mediated by β-ARs [5].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Besides, dopamine significantly increased the levels of the chemokine IL-8 in THP-1 macrophages, which is similar to the observations made by Gaskill [11] in LPS-stimulated human mononuclear-derived macrophages. The stimulatory effect of dopamine on the secretion of IL-8 was partially reversed by the β-adrenergic blocker propranolol, similar to the effect previously described in keratinocytes, where dopamine stimulated the production of IL-6 and IL-8 mainly mediated by β-ARs [5].…”
Section: Discussionsupporting
confidence: 79%
“…In addition to MMPs, keratinocytes and macrophages produce different inflammatory molecules such as cytokines [6, 44]. Gaskill et al [11] demonstrated that dopamine (2 × 10 –8 to 2 × 10 –5 M) may either decrease or increase the production of cytokines (IL-6, CCCL-2, IL-8, IL-10, TNF-α) by PBMC-derived macrophages and depending on whether the cells are activated or not by bacterial LPS. However, it is known that the effect of dopamine depends not only on the activation status of the cell population involved, but also on the concentration of the catecholamine as well as on the mechanism involved (type of receptor/oxidative mechanism).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, SKI-417616 inhibits the phosphorylation of ERK in response to dopamine but does not affect the repression of cAMP signaling, a second arm of DRD4 downstream signaling. The expression and activity of dopamine receptors are typically considered to be specific to neurons; however, several recent reports have demonstrated expression of dopamine receptors on rodent and human macrophages (32,33), a primary target cell of DENV infection. Although the exact mechanism has not yet been elucidated, dopamine receptors expressed on macrophages appear to play an important role in regulating cytokine production and modulating immune function (32).…”
Section: Discussionmentioning
confidence: 99%
“…The expression and activity of dopamine receptors are typically considered to be specific to neurons; however, several recent reports have demonstrated expression of dopamine receptors on rodent and human macrophages (32,33), a primary target cell of DENV infection. Although the exact mechanism has not yet been elucidated, dopamine receptors expressed on macrophages appear to play an important role in regulating cytokine production and modulating immune function (32). Whether this function of macrophage-expressed dopamine receptors is related to the effect of DRD4 inhibition by DHBTs on DENV infection is unclear and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%